Six-month survival of critically ill patients with HIV-related disease and tuberculosis: a retrospective study. Issue 1 (December 2016) - Pecego, Ana; Amancio, Rodrigo; Ribeiro, Camila; Mesquita, Emersom; Medeiros, Denise; Cerbino, José; Grinsztejn, Beatriz; Bozza, Fernando; Japiassu, Andre
Abstract Background Tuberculosis is one of the leading causes of death from infectious diseases worldwide, mainly after the human immunodeficiency virus (HIV) epidemics. Patient with HIV-related illness are more likely to present with severe TB due to immunosuppression. Very few studies have explored HIV/TB co-infection in critically ill patients. The goal of this study was to analyze factors associated with long-term mortality in critically ill patient with HIV-related disease coinfected with TB. Methods We conducted a retrospective study in an infectious disease reference center in Brazil that included all patient with HIV-related illness admitted to the ICU with laboratory-confirmed tuberculosis from March 2007 until June 2012. Clinical and laboratory variables were analyzed based on six-month survival. Results Forty-four patients with HIV-related illness with a confirmed diagnosis of tuberculosis were analyzed. The six-month mortality was 52 % (23 patients). The main causes of admission were respiratory failure (41 %), severe sepsis/septic shock (32 %) and coma/torpor (14 %). The median time between HIV diagnosis and ICU admission was 5 (1–60) months, and 41 % of patients received their HIV infection diagnosis ≤ 30 days before admission. The median CD4 count was 72 (IQR: 23–136) cells/mm3 . The clinical presentation was pulmonary tuberculosis in 22 patients (50 %) and disseminated TB in 20 patients (45.5 %). No aspect of TB diagnosis or treatment was different between survivors and nonsurvivors. Neurological dysfunction was more prevalent among nonsurvivors (43 % vs. 14 %, p  = 0.04). The nadir CD4 cell count lower than 50 cells/mm3 was independently associated with Six-month mortality (hazard ratio 4.58 [1.64–12.74], p  < 0.01), while HIV diagnosis less than three months after positive serology was protective (hazard ratio 0.27, CI 95 % [0.10–0.72], p  = 0.01). Conclusion The Six-month mortality of HIV critically ill patients with TB coinfection is high and strongly associated with the nadir CD4 cell count less than 50 cels/mm3 .